PENINGKATAN KEAKTIFAN DAN HASIL BELAJAR IPADENGAN MODEL PEMBELAJARAN KOOPERATIF TIPE GROUP INVESTIGATION - Susanti Susanti; Hidayati Hidayati; Widowati Pusporini (N A T U R A L: Jurnal Ilmiah Pendidikan IPA, 2014)
The aim of this research is to increase activeness and study result of science through cooperative learning model with group investigation typeof students grade VIII C SMP Negeri 11 Yogyakartain year 2013/2014. The kind of this research is Action Research. The subject of this research is C class the second grade Student at SMP Negeri 11 Yogyakarta that amount of 32 student. The object of this research is activeness and study result of science through cooperative learning model with group investigation type. The instrument of this research involved observation sheet, test, interview, and documentation. The result of this research showed that after implementation of cooperative learning model with Group Investigation type, activeness and study result science increased. Student’ activeness increased from pre cycle as 45,31% become 62,97% on first cycle and increased more as 84,69% on second cycle. Whereas the result of student’ also increased. The average  of student’ grade from the first grade as 46,94 on the student’ (6,25%) that fullfilles KKM increased to 60,16 on 11 student’ (34,38%) that fullfilles KKM on first cycle. Where as on second cycle the average of student’ grade increased to 84,38 on 26 student’s (81,25%) that fullfilled KKM.